Situación económica productiva del cultivo de café (Coffea Arábica L.) en la provincia de Los Ríos. - Mina Villena, Luis Fernando (2022)
The cultivation of coffee (Coffea Arabica L.) is known as a coffee tree or coffee-producing plant, this is considered a bush that develops in areas where the climatic conditions are optimal for its good growth. Coffee is one of the important crops, its harvest is used to make a drink that is obtained from the roasted and ground grains of the fruits of the plant. This product is one of the most commercialized and one of the three most consumed beverages in the world. Coffee plantations can reach a high production and a high economic yield of agricultural work, which more than sixty percent of production is in the coastal region and generates a great source of work for many families. Ecuador is a country rich in diversity and a beneficiary of climatic factors that help an excellent production of coffee, as it has become a staple product within our country. The problem that this research addresses is due to the low production and commercialization of coffee cultivation at the level of the province of Los Ríos, not only raw product, but also in the commercialization of already processed coffee products. This is due to the high price of fertilizers, the fall in international prices, the low productivity of coffee plantations and the poor quality of the grain, which leads to a considerable decrease in price.